2020
DOI: 10.3389/fimmu.2020.575890
|View full text |Cite
|
Sign up to set email alerts
|

Thrombomodulin as a Physiological Modulator of Intravascular Injury

Abstract: Thrombomodulin (TM), which is predominantly expressed on the endothelium, plays an important role in maintaining vascular homeostasis by regulating the coagulation system. Intravascular injury and inflammation are complicated physiological processes that are induced by injured endothelium-mediated pro-coagulant signaling, necrotic endothelialand blood cell-derived damage-associated molecular patterns (DAMPs), and DAMPmediated inflammation. During the hypercoagulable state after endothelial injury, TM is releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
63
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 119 publications
0
63
0
1
Order By: Relevance
“…The recombinant, soluble form of TM (comprising the extracellular domain of TM) is thought to primarily affect thromboinflammation through the neutralization of several damage-associated molecular patterns, including histones and HMGB1, as well as activated complement factors. 43 Reversal of laboratory indices of DIC during treatment with recTM was observed, as well as a reduction in hemorrhagic death. 44 However, DIC in sepsis is different from leukemias in the levels of protein C, and it may be difficult to predict the risk of bleeding related to recTM infusion and generation of activated protein C, in the latter patients.…”
Section: Acute Promyelocytic Leukemia and All-trans Retinoic Acidmentioning
confidence: 89%
“…The recombinant, soluble form of TM (comprising the extracellular domain of TM) is thought to primarily affect thromboinflammation through the neutralization of several damage-associated molecular patterns, including histones and HMGB1, as well as activated complement factors. 43 Reversal of laboratory indices of DIC during treatment with recTM was observed, as well as a reduction in hemorrhagic death. 44 However, DIC in sepsis is different from leukemias in the levels of protein C, and it may be difficult to predict the risk of bleeding related to recTM infusion and generation of activated protein C, in the latter patients.…”
Section: Acute Promyelocytic Leukemia and All-trans Retinoic Acidmentioning
confidence: 89%
“… 8 , 9 Endothelial cells express key molecules that regulate the balance between hemostasis and thrombosis such as thrombomodulin and von Willebrand factor (VWF). 9 , 10 , 11 , 12 In COVID-19 patients, elevated plasma levels of soluble VWF, thrombomodulin, intercellular adhesion molecule 1 (ICAM-1), vascular adhesion molecule 1 (VCAM-1), and P-selectin have been shown, suggesting endothelial cell activation and dysfunction. 13 , 14 , 15 , 16 Several researchers predicted that vascular endothelial cells in COVID-19 increased adhesion molecule expression for platelet and leukocyte migration and pro-inflammatory cytokine and chemokine production.…”
Section: Introductionmentioning
confidence: 99%
“… 26 , 27 , 28 , 29 , 30 Furthermore, endothelial transmembrane molecules such as thrombomodulin and ICAM-1 are generally cleaved by enzymes and released into the blood in diseased conditions, suggesting that a transcriptional profile of endothelial cells would not reflect their dysfunctional phenotype during COVID-19. 11 , 12 , 31 Also, it remains unclear whether endothelial cell dysfunction and damage in COVID-19 are induced by direct SARS-CoV-2 infection or indirectly through pathologic conditions such as hypoxia and pro-inflammatory cytokine milieu. Some studies have shown ACE2 expression on endothelial cells with limited evidence for the direct infection by SARS-CoV-2.…”
Section: Introductionmentioning
confidence: 99%
“…It is part of the anticoagulant protein C system, in which thrombomodulin binds with thrombin and promotes the cleavage of protein C and thrombin activatable fibrinolysis inhibitor, thereby inhibiting coagulation (Wenzel et al, 2014). Additionally, it interferes with inflammation, stabilizes barrier function, and promotes angiogenesis under pathological conditions (Watanabe-Kusunoki et al, 2020). Clec10a is a member of the C-type lectin receptor family and is expressed by myeloid APC, such as dendritic cells and macrophages (Ilarregui et al, 2019).…”
Section: Discussionmentioning
confidence: 99%